Blood stem cell-forming haemogenic endothelium in zebrafish derives from arterial endothelium - Florian Bonkhofer (Nature Portfolio, 2019)
HSCs emerge from haemogenic endothelium (HE) in the dorsal aorta but whether these tissues share a common lineage is unclear. Here, the authors use a zebrafish runx1 reporter to show that HE maintains an arterial gene expression profile in the absence of Runx1, suggesting the aortic endothelium as a precursor of HE.